1996
DOI: 10.1021/ma951797v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Norbornenylpoly(ethylene oxide) Macromonomers and Their Ring-Opening Metathesis Polymerization

Abstract: This work focuses on the synthesis and the ring-opening metathesis polymerization of α-norbornenylpoly(ethylene oxide) macromonomers. Although obtained in 100% yield and with a narrow distribution of molar masses, the polymacromonomers exhibit degrees of polymerization that are systematically higher than expected. The reasons for this feature are thoroughly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 8 publications
2
107
0
1
Order By: Relevance
“…Recently, Heroguez and coworkers have reported that ROMP was the method of choice to prepare polymacromonomers within high yields and with precise control of the size, which is the major problem in the synthesis of this type of multibranched structures. 8 Based on the living/controlled ROMP, different combinations of polystyrene and poly(ethylene oxide) macromonomers, thus random and block copolymacromonomers, have been prepared by copolymerization of the parent norbornenyl-macromonomers. In this work, we have investigated the homopolymerization of the ␣-norbornenyl PCL macromonomers in order to prepare multibranched polyesters (Scheme 3).…”
Section: Ring-opening Polymerization Of the Pcl Macromonomersmentioning
confidence: 99%
“…Recently, Heroguez and coworkers have reported that ROMP was the method of choice to prepare polymacromonomers within high yields and with precise control of the size, which is the major problem in the synthesis of this type of multibranched structures. 8 Based on the living/controlled ROMP, different combinations of polystyrene and poly(ethylene oxide) macromonomers, thus random and block copolymacromonomers, have been prepared by copolymerization of the parent norbornenyl-macromonomers. In this work, we have investigated the homopolymerization of the ␣-norbornenyl PCL macromonomers in order to prepare multibranched polyesters (Scheme 3).…”
Section: Ring-opening Polymerization Of the Pcl Macromonomersmentioning
confidence: 99%
“…There are many approaches to these macromolecules, each with their own obstacles (24,25). In the "grafting through" or macromonomer (MM) method, the side chain containing a terminal monomer is synthesized first and subsequently polymerized to yield the resulting brush polymer (24,26). This approach ensures complete grafting of a welldefined side chain on every backbone monomer unit; however, it requires an extremely robust polymerization mechanism to achieve high MW while maintaining control of the PDI (25).…”
mentioning
confidence: 99%
“…[123][124][125][126][127][128][129][130][131] It has been believed for a long time that such densely branched polymers cannot be synthesized by means of "grafting-onto" method because of serious steric hindrance of branches. However, Deffieux and Schappacher have recently reported the first successful synthesis of such densely branched polymers by the coupling reaction of poly(2-chloroethyl vinyl ether) with polystyryllithium based on a graftingonto method.…”
Section: Synthesis Of Densely Branched Polymers With Starlike Structuresmentioning
confidence: 99%